Integrated multimetric assessment of mangrove-seagrass-plankton systems across spatial gradients in Banyuwedang Bay, Bali, Indonesia - I PUTU SUGIANA; I MADE ABDI JANAGUNA; SAMUDRA ALFATIHA; I MADE SAKA WIJAYA; I GEDE ADHITIYA YASA; I WAYAN GDE SUTASOMA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Sugiana IP, Janaguna IMA, Alfatiha S, Wijaya IMS, Yasa IGA, Sutasoma IWG. 2026. Integrated multimetric assessment of mangrove-seagrass-plankton systems across spatial gradients in Banyuwedang Bay, Bali, Indonesia. Biodiversitas 27 (4): d270416. https://doi.org/10.13057/biodiv/d270416. North Bali coastal waters host interconnected mangrove-seagrass-plankton systems that respond to spatial gradients in physicochemical conditions. This study provides a multimetric baseline assessment integrating environmental parameters with mangrove, seagrass, and plankton indicators across three stations (S1-S3) in Banyuwedang Bay (November 2025), emphasizing spatial ecological patterns rather than inferential relationships. The analysis integrates environmental parameters with ecological indicators of mangroves (Mangrove Health Index, MHI), seagrass (Seagrass Ecological Quality Index, SEQI), and plankton communities (diversity H’, evenness J, and dominance C). Environmental conditions varied spatially, with higher suspended solids at the inner bay and increasing temperature, salinity, and conductivity toward the outer bay. Mangrove ecosystems were consistently classified as excellent (MHI: 67.45-75.98), indicating structurally stable stands despite differences in species composition. In contrast, seagrass meadows exhibited moderate ecological condition (SEQI: 0.63-0.67), reflecting variation between species richness at the inner station and higher coverage at the mid-bay station. Plankton communities showed moderate diversity (phytoplankton H’: 1.31-1.75; zooplankton H’: 0.83-1.80) with localized dominance at the mid-bay station, indicating spatial heterogeneity in community structure. Diatoms dominated across stations, while cyanobacteria increased at one location, suggesting spatial variability associated with environmental gradients. Zooplankton communities displayed relatively high evenness across stations. Overall, the integrated multimetric approach reveals that coastal ecosystems in Banyuwedang Bay remain functionally intact but exhibit clear spatial heterogeneity along the inner-outer gradient. This study provides an integrated baseline framework linking benthic and pelagic indicators for future monitoring and adaptive coastal management in relatively low-disturbance tropical bays.